Putting Health Services Research into Practice - Wai Ling Chow GDFM (Singapore), MBBS (Singapore); Jeremy Fung Yen Lim MBBS, MPH (Proceedings of Singapore Healthcare, 2011)
Health services research (HSR) seeks to shed light on healthcare as a system, focusing on the cost of, the quality of and access to health services. While there is recognition that the practice of medicine should be evidence-based, there has been limited progress in implementing evidence-based healthcare management. This review proposes a conceptual framework of putting HSR into practice through culture change; human capability capacity building and sustaining change via a supportive environment and reinforcing infrastructure